SPEECH STYLES FOUND IN THE OBAMA VS. ROMNEY FIRST PRESIDENTIAL DEBATE - Kasmawati, Kasmawati; Weda, Sukardi; Mahmud, Murni (Journal of English Literature and Linguistic Studies, 2025)
This research is qualitative descriptive. The purpose of this study is to identify the speech style utilized in Obama and Romney's first presidential debate and to determine the function of speech style. Primary and secondary data sources were used in this investigation. Watching, obtaining transcripts, reading transcripts, and evaluating data in the areas of language style and function were the data gathering strategies employed in this study. The collected data was then evaluated using Martin Joos (1976) theory of speech styles and Janet Holmes (2013) theory of speech functions. According to the findings of this study, the researcher discovered five types of speech styles present in President Barack Obama's first debate against Mitt Romney, namely frozen, formal, consultative, relaxed, and intimate, as well as five language functions identified in the first debate. President Barack Obama's discussion with Governor Mitt Romney was expressive, directional, referential, metalinguistic, and phatic.